2021
DOI: 10.1155/2021/8899274
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Revealed the Characteristics of Key Proteins Involved in the Regulation of Inflammatory Response, Leukocyte Transendothelial Migration, Phagocytosis, and Immune Process during Early Lung Blast Injury

Abstract: Previous studies found that blast injury caused a significant increased expression of interleukin-1, IL-6, and tumor necrosis factor, a significant decrease in the expression of IL-10, an increase in Evans blue leakage, and a significant increase in inflammatory cell infiltration in the lungs. However, the molecular characteristics of lung injury at different time points after blast exposure have not yet been reported. Therefore, in this study, tandem mass spectrometry (TMT) quantitative proteomics and bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To understand the changes in inflammation during the immediate inflammatory response within 24 h, we monitored the control group and the injury groups at 0 and 24 h using serological ELISA. Serum levels of IL-6 and IL-8 increased rapidly post-injury and then decreased at 24 h ( 27 ). Some researchers found that the levels of proinflammatory factors such as IL-6, and IL-8 were significantly increased in BALF and serum of ALI/ARDS children.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the changes in inflammation during the immediate inflammatory response within 24 h, we monitored the control group and the injury groups at 0 and 24 h using serological ELISA. Serum levels of IL-6 and IL-8 increased rapidly post-injury and then decreased at 24 h ( 27 ). Some researchers found that the levels of proinflammatory factors such as IL-6, and IL-8 were significantly increased in BALF and serum of ALI/ARDS children.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1, ICAM-1, and E-selectin were reportedly upregulated in an experimental sepsis model of human umbilical vein endothelial cells [ 24 ]. ICAM-1 mRNA can also interact with Itgal, which mainly encodes a key T cell integrin, lymphocyte function-associated antigen 1(LAF1), and is considered to be an important factor in regulating T cell activation and migration [ 8 ]. Itgal also plays important roles in recruiting cells to sites of inflammation and has downstream effects on cellular signaling [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory responses have been shown to be activated in explosion-induced injury [ 7 ]. In our previous study, proteomic analysis helped confirm that blast lung injury induced early inflammatory response through regulating the expression of key proteins involved in the inflammatory process [ 8 ]. Additionally, expression levels of leukocyte adhesion- (LA-) related proteins were increased by blast exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Among all inflammatory cytokines we concentrate, IL-18 plays an important role in early inflammatory response, it is reported to promote neutrophils aggregation and lympho T cell proliferation, and mediate cytotoxic reactions (32). TNF-α is located in the upstream of the inflammatory response and mediate the synthesis of various inflammatory cytokines (14). TGF-β can inhibit cell proliferation and induce cell differentiation or apoptosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…When the lung is exposed by blast wave, a series of physiological stress responses such as oxidative stress, inflammation, and edema often occur (10)(11)(12). Moreover, some researchers used mice to establish a blast lung injury model in vivo based on the shock tube to explore the mechanism of blast lung injury, and found that the blast wave could cause inflammation, oxidative stress and apoptosis in the lung tissues of mice (13,14). Mechanistically, damage in alveolar epithelial cells is the main cause of oxidative stress and inflammatory response, it plays an important role in blast wave-induced lung injury (15).…”
Section: Introductionmentioning
confidence: 99%